Uptake and survival of enteric viruses in the blue crab, Callinectes sapidus. - Hejkal, T W (1981)
Uptake of poliovirus 1 by the blue crab, Callinectes sapidus, was measured to assess the likelihood of contamination by human enteric viruses. Virus was found in all parts of the crab within 2 h after the crab was placed in contaminated artificial seawater. The highest concentrations of virus were found in the hemolymph and digestive tract, but the meat also contained virus. The concentration of virus in the crabs was generally less than in the surrounding water. Changes in salinity did not substantially affect the rate of accumulation. An increase in temperature from 15 to 25 degrees C increased the rates of both uptake and removal. Poliovirus survived up to 6 days in crabs at a temperature of 15 degrees C and a salinity of 10 g/kg. When contaminated crabs were boiled, 99.9% of poliovirus 1, simian rotavirus SA11, and a natural isolate of echovirus 1 were inactivated within 8 min. These data demonstrate that viruses in crabs should not pose a serious health hazard if recommended cooking procedures are used.